Pengaruh Latihan Plyometrik Terhadap Hasil Lompat Jauh Pada Siswa SMAN 1 Srengat - Iqbal Naufal Ahmad; Heri Wahyudi; Testa Adi Nugraha; Catur Supriyanto (Journal of Student Research, 2024)
This study aims to analyze the effect of plyometric exercises in the form of jumping using one leg and jumping using two legs with the results of jumping in long jump. This research was conducted at SMAN 1 Srengat with 30 students for 18 meetings within 6 weeks. This study used quantitative methods with experimental research types using pre-test and post-test designs. The results obtained in this study are plyometric exercises that play a role in achieving long jump achievements. The results obtained there was a significant average difference between the pre-test results and post-test results in the plyometric exercise group. So it can be proven by the t-test value in the jumping group using one leg of -10.389 < -2.262 and the sig (2-tailed) value of 0.000 is smaller than 0.05, the jumping group uses two legs of -6.266 < -2.262, and the sig (2-tailed) value of 0.000 is smaller than 0.05 and the control group is -1.875>-2.262 and the sig (2-tailed) value of 0.093 is greater than 0.05 . This study can have a significant influence on the provision of plyometric exercises on the method of jumping using one leg and jumping using two legs